2017
DOI: 10.1007/s10815-017-0957-8
|View full text |Cite
|
Sign up to set email alerts
|

Human sperm Toll-like receptor 4 (TLR4) mediates acrosome reaction, oxidative stress markers, and sperm parameters in response to bacterial lipopolysaccharide in infertile men

Abstract: These findings indicate that human spermatozoa express TLR4 and respond to LPS stimulation with alterations in viability, motility, and the acrosome reaction implicating reactive oxygen species (ROS) production in sperm samples from infertile patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…On the other hand, the caput epididymal inflammation, as reflected by the increased expression of IL-1β, CXCL-10, MCP-1 and NF-κBp65, could be a likely ‘culprit’ responsible for the reduced sperm counts and motility in the HFD-FMT mice. Multiple studies have demonstrated that epididymal inflammation condition negatively affects sperm quality 38 39 47–52. Global elevation of NF-κB p65 expression has been shown to exert anti-inflammatory and antiobesity effects by increasing energy expenditure 53.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the caput epididymal inflammation, as reflected by the increased expression of IL-1β, CXCL-10, MCP-1 and NF-κBp65, could be a likely ‘culprit’ responsible for the reduced sperm counts and motility in the HFD-FMT mice. Multiple studies have demonstrated that epididymal inflammation condition negatively affects sperm quality 38 39 47–52. Global elevation of NF-κB p65 expression has been shown to exert anti-inflammatory and antiobesity effects by increasing energy expenditure 53.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have well established the causal relationship between the endotoxaemia/epididymal inflammation and low sperm motility/spermatogenic dysfunction in both animal models and humans 38 39 47–52. Intraperitoneal administration of lipopolysaccharides (LPS) could elevate the expression of pro-inflammatory cytokines, such as IL-1β, IL-6 and CXCLi2 in the epididymis and testis of roosters48 and increase the level of IL-18 in mouse testes 49.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its result is statistically significant ( p < 0.001), with MD values of 1.42 µmol/L and heterogeneity coefficient of 99.75% [ 57 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. MDA values have been shown to be significantly higher in men with varicocele or infective diseases in the urogenital tract, which correlates with decreased sperm motility [ 76 ] and higher percentages of necrotic and apoptotic sperm, and heat stress [ 77 ]. This phenomenon can be explained by reduced heat shock proteins and B-cell lymphoma 2 (BCL2) expression, increased BCL2-associated X protein (BAX) expression and higher polymorphism of genes encoding S-glutathione transferase or nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be determined whether spermatozoa bearing FASLG contribute to immunoprivileged status within the seminiferous tubule (Li, Wang, & Han, ; Zhao et al, ). Though the role of TLR10 in the developmental process of spermatogenesis (Saeidi et al, ) has been reported, the immune regulatory functions of TLR in testis and spermatozoa quality have yet to be detailed (Li et al, ; Sahnoun et al, ; Girling and Hedger, ). TLR initiates the innate immune response through cytokines including tumor necrosis factor α (TNFA), interleukin 1 (IL1), IL6, and its regulation is essential for the protection of germ cell from immune attack (Zhao et al, ) and pathogenic molecules (Bhushan et al, ; Sahnoun et al, ).…”
Section: Testicular Immune Mechanismmentioning
confidence: 99%